A Forma do Mobiliário dos Espaços de Aprendizagem e a Arquitetura Escolar - Interação e Relação com as Aprendizagens - Joana Maria Marques do Vale (2018)
FIRST CHAPTER - THE REINTERPRETATION Nuclear subjects of social and political context were analyzed, such as the educative reforms since the introduction of the open area schools (P3), from 1965, and was built a relationship with the reality of today's school, based on the adaptation of international pedagogical models, which follow the free schools model. The chapter was finalized reinterpreting the new approaches of architectonic project and the new approaches of learning space furniture, and was done a research on the featured assessment tools. SECOND CHAPTER - THE VERIFICATION Analyzing the habits of the students on the learning space as a relationship and not as an influence allowed, to understand that the relationship stablished here, between architecture and design had origin from shape. The physical and measurable space affect the project development, as an architectural project. Which in turn allows to establish the physical contact with the habitant, in this case the school community. By using the learning space, the school community creates an interaction which is stablish between the utilization of the school furniture and the physical space. Being this relationship acknowledged, one can say that the space is related with the architecture, such as the habits of students ar e related with the school community, and the school furniture is related with the design. Briefly, these thematic gave rise to 3 fundamental pillars: the shape of the furniture, the learning space and pedagogies. But how can one justify the growing emergence of innovative learning environments in other countries in the last few decades? The answer consists of considering that different educational models have been implemented. THIRD CHAPTER - THE RESULTS In this chapter the observation took place. For this , it was essential to lay down criteria, in order to select the case examples and case studies. In a first stage, several programs and initiatives that had been promoted by educative reforms were analyzed. In a second stage, the projects with the learning space furniture suitable for the educative model (active) were selected, projects which would offer diverse and pedagogical learning spaces. As for the educational stage, the second cycle and the third cycle (or equivalent) were kept, as originally planned, due to their own complexity, related to the student's age range and related to subject plurality. Besides, the way these interact and combine to humanize and improve the space was also a factor taken into account. Exceptionally, more educational project s were selected due to their teaching and learning space particularities, from a kindergarten to a first cycle school, which allowed to do a comparative analysis. The functionality of the learning environments was studied thoroughly and made possible to set a final framework. The results observation and analysis were a defining step to the real comprehension of both design and architectural needs.